2014
DOI: 10.2298/mpns1406154n
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of success of psoriasis treatment with standard therapeutic modalities and balneotherapy

Abstract: Introduction. Psoriasis is a chronic, inflammatory, immune-mediated skin disease. In addition to standard therapeutic modalities (antibiotics, cytostatics, phototherapy, photochemotherapy and retinoids), nonstandard methods can be used in the treatment of psoriasis. This includes balneotherapy which is most commonly used in combination with therapeutic resources. The aim of this research was to determine the length of remission of psoriasis in patients treated with standard therapeutic modalities, balneotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Mineral waters contain substances such as sulfur and salt that may be very effective in treating skin diseases. 46 Sulfate sources can be used in many chronic inflammatory diseases due to the properties of keratolytic, antifungal, antioxidant, and anti-inflammatory and antiproliferative effects. 38,65,66 Hydrogen sulfide is a small permeable gas that can enter the skin's intracellular molecules and have many effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral waters contain substances such as sulfur and salt that may be very effective in treating skin diseases. 46 Sulfate sources can be used in many chronic inflammatory diseases due to the properties of keratolytic, antifungal, antioxidant, and anti-inflammatory and antiproliferative effects. 38,65,66 Hydrogen sulfide is a small permeable gas that can enter the skin's intracellular molecules and have many effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide can inhibit the proliferation of T lymphocytes and interleukin-8, as well as decrease cellular adhesion. 33,46,66 Lee et al 67 showed that balneotherapy by immunomodulatory leads to a decrease in the production of Th1 and Th2-dependent cytokines such as intercellular adhesion molecule 1 expression, and E-selectin can be in human endothelial cells and thus reduce the complications of this disease. Also, some studies have shown that in in vitro conditions, balneotherapy is able to modulate the immune system due to the high amount of sulfur in its composition.…”
Section: Discussionmentioning
confidence: 99%
“…Although no data was obtained regarding length of the disease, they varied from one to 60 years, the most common values being centered around 20-30 years. Treatment length was most commonly 3-4 weeks, although some balneotherapy interventions took 6 or 8 weeks [22][23][24], whereas some patients under climatotherapy followed this treatment for as little as 6 days [25]. It is worth mentioning that the study of Langeland and that by Wahl employed the same patient population based on their characteristics [26,27].…”
Section: Patient Populationsmentioning
confidence: 99%
“…Other locations that have climatotherapeutic or balneotherapeutic (bathing in hot springs) effects are in the Black Sea, Nord Sea, Baltic Sea, Canary Islands, Kangal Hot Springs in Turkey, or the Blue Lagoon in Iceland, but the evidence regarding each of these sites is lacking when compared to the Dead Sea [11,18,70,110,111]. Balneotherapy alone or in combination with standard treatment or phototherapy has repeatedly proven to be more effective than standard treatment alone [23,[85][86][87][88][89]. Geothermal sea water balneotherapy and narrowband UVB (NB-UVB) light therapy is apparently more effective in attaining clinical and histological amelioration, results in longer remission time and allows for lower UV doses than NB-UVB therapy alone [21].…”
Section: Balneotherapy and Climatotherapymentioning
confidence: 99%
“…Today the Kangal Spring is designated as a certified thermal health center by the Turkish Ministry of Health and offers a 21-day treatment for psoriasis for visitors from around the world. This therapy provides an alternative to other forms of biotherapies which have been shown to improve psoriasis such as balneotherapy and thalassotherapy or treatment with seawater and mineral water, respectively [2,3]. Anecdotally, ichthyotherapy can also be used to treat skin diseases other than psoriasis, such as acne and eczema [1].…”
Section: Introductionmentioning
confidence: 99%